Optimal portfolio management for individual pension plans - Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2005)
We explore the various arguments for and against the recommendation that younger households should invest a larger share of their pension wealth in risky assets. The ability of young agents to compensate their financial losses by saving more during their career provides the strongest argument in favour of younger people investing more aggressively in the stock market. Meanreversion in stock returns yields another argument. However, the uninsurability of the risky human capital goes in the opposite direction, together with the imperfect knowledge that young investors have about the distribution of asset returns.
Keywords: G11; 330; dynamic portfolio choice; pension plan; retirement; time horizon; Private Rentenversicherung; Kapitalanlage; Portfolio-Management; Lebensalter; Entscheidung bei Unsicherheit; Aktie; Verdienstausfall; Theorie